Incidence of the caste system in the development of India (2014)
India is a country where daily living with disparities and contradictions. In its 28 states and seven territories, it houses a multitude of ethnicities from diverse cultures, languages and religions. India stands out for its rapid economic growth, which has been even greater than that of some countries in the Asia Pacific; However, in terms of social indicators, there are still obstacles to overcome. One of the main aspects that has influenced its slow development is the inequity, which is partly due to the caste system, a social structure predominantly for more than 3,500 years in the subcontinent.